THE USE OF AJAX TECHNOLOGY IN NEW STUDENTS REGISTRATION WEBSITE AT MATANA UNIVERSITY - Himawan Himawan; Ignatius Joko Dewanto; Muhammad Ghurfata Rumara (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2017)
Formerly, website technology only used HTML to display static content (web 1.0), then in the modern era, modern website was developed (web 2.0). The use of HTML language was combined with dynamic web programming languages such as PHP, ASP.Net, and JSP. However, in order to make the website page become more interactive and responsive, the use of dynamic web programming languages was not enough, therefore a technology that called as AJAX was created. This application is able to make website page becomes more responsive and interactive. The use of AJAX technology in modern website applications can also make the website page load faster and save the bandwidth usage of the internet network connection due to the asynchronous data transfer process between the client and the server. This study was aimed to fi nd out the mechanism of data transfer process and the comparison 99 of access speed level between client computer and the server (web and database server), especially on the website page using AJAX technology. This study used case study method and literature review analysis. Through this research, the AJAX engine model contained in JavaScript programming can be analyzed to produce better level of connectivity between client computers and the server.